2002
DOI: 10.1046/j.1365-8711.2002.06043.x
|View full text |Cite
|
Sign up to set email alerts
|

Another interpretation of the power-law-type spectrum of an ultraluminous compact X-ray source in IC 342

Abstract: The ultraluminous compact X‐ray sources (ULXs) generally show a curving spectrum in the 0.7–10 keV ASCA bandpass, which looks like a high‐temperature analogue of the disc‐dominated high/soft‐state spectra seen in Galactic black hole binaries (BHBs) at high mass accretion rates. Several ULXs have been seen to vary, and to make a transition at their lowest luminosity to a spectrum which looks more like a power law. These have been previously interpreted as the analogue of the power‐law‐dominated low/hard state i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 41 publications
(63 reference statements)
6
65
0
Order By: Relevance
“…This is equivalent to saying that the radius of the emitting region is not constant between sources or for the same source at various epochs. A constant inner-disk radius Rin ≈ 1.19rin ≈ RISCO (radius of the innermost stable circular orbit) is usually taken as the defining property of the high/soft they are more likely to be high-inclination objects, as discussed in Section 5.3. state in luminous BHs at accretion rates a few percent of the Eddington limit (Kubota, Done & Makishima 2002;Remillard & McClintock 2006). The IMBH scenario was based on the interpretation of the thermal component as disk emission in the high/soft state; however, we see that the thermal component in ULSs does not behave like a standard disk in the canonical high/soft state.…”
Section: X-ray Spectral Propertiesmentioning
confidence: 76%
“…This is equivalent to saying that the radius of the emitting region is not constant between sources or for the same source at various epochs. A constant inner-disk radius Rin ≈ 1.19rin ≈ RISCO (radius of the innermost stable circular orbit) is usually taken as the defining property of the high/soft they are more likely to be high-inclination objects, as discussed in Section 5.3. state in luminous BHs at accretion rates a few percent of the Eddington limit (Kubota, Done & Makishima 2002;Remillard & McClintock 2006). The IMBH scenario was based on the interpretation of the thermal component as disk emission in the high/soft state; however, we see that the thermal component in ULSs does not behave like a standard disk in the canonical high/soft state.…”
Section: X-ray Spectral Propertiesmentioning
confidence: 76%
“…Another possibility is that X-11, X-16, and X-37 are stellarmass black holes in the ''very high'' state (see the reviews mentioned previously; see also Kubota et al 2002). Certainly, if ULXs behave similarly to Galactic stellar-mass black holes, it is reasonable to expect that this state holds at the luminosities observed.…”
Section: Discussionmentioning
confidence: 96%
“…Such strong Comptonization is believed to occur in Galactic jet sources (e.g., GRO J1655À40, Kubota, Makishima, & Ebisawa 2001b) and possibly in an ULX in IC 342 (Kubota et al 2002). Kubota et al (2002) reanalyzed the ASCA spectrum of source 1 in IC 342 observed in 2000. The spectrum can be fitted with either a power law (À ¼ 1:73 AE 0:06, modified by an ionized Fe K edge at 8:4 AE 0:3 keV) or a Comptonized blackbody with an inner disk temperature of kT in ¼ 1:1 AE 0:3 keV.…”
Section: Ulxs With a Power-law Spectrummentioning
confidence: 99%